Geographical Indication, Agricultural Products Export and Urban–Rural Income Gap - Sihui Zhang; Yong Sun; Xuzhou Yu; Yafeng Zhang (Agriculture, 2023)
The Nineteenth National Congress of the Communist Party of China put forward the implementation of a rural revitalization strategy, which is an important way to achieve common prosperity for all the people, as promoting farmers’ income increase and narrowing the urban–rural income gap are key to promoting rural revitalization and common prosperity. So, under the background of vigorously promoting the rural revitalization strategy in China, it is very important to explore the effect and realization mechanism of geographical indication (GI) on reducing the urban–rural income gap. Based on the statistical data of 31 provinces in China from 2008 to 2019, this empirical study uses the spatial Durbin model (SDM) to analyze the relationship between GI and urban–rural income gap, and the stepwise regression method is used to explore the mediating effect of agricultural product exports on it. The results show that: (1) The potential economic value of GI branding can reduce the urban–rural income gap, and each additional unit of GI in this region will reduce the urban–rural income difference of this region by 0.160 units, and the urban–rural income difference of neighboring regions by 0.133 units. The result is still consistent after changing the proxy variable of urban–rural income gap for robustness test; (2) The brand effect of GI can form a stronger competitive advantage in foreign trade and promote the export level of agricultural products; (3) GI can narrow the urban–rural income gap through the export of agricultural products, and agricultural product export plays an important mediating effect. In the future, the government should not only strengthen the management and protection of GI but also actively market GI products. Promoting the international mutual recognition and mutual protection of GI can ensure the agricultural product export of GI and improve the foreign trade level of GI.